Effect of Seasonal Variation on Relapse Rate in Patients With Relapsing-Remitting Multiple Sclerosis in Saudi Arabia - Makkawi, Seraj; Aljabri, Ammar; Bin Lajdam, Ghassan; Albakistani, Ammar; Aljohani, Abdulrahman; Labban, Suhail; Felemban, Razaz (Frontiers in Neurology, 2022)
Multiple sclerosis (MS) is becoming a global subject of study in which some demographic variations are thought to be correlated with its activity. Relapsing-remitting multiple sclerosis (RRMS) is the most common demyelinating disorder, characterized by periods of exacerbating attacks, followed by partial or complete remission. Several factors might play a role in disease progression and relapse frequency, such as vitamin D, ultraviolet B radiation, estrogen levels, smoking, obesity, and unhealthy lifestyles. In this study, we identified the relationship between seasonal variation and relapse rate and correlated the latter with sex, age, and vitamin D levels in patients with RRMS in Jeddah, Saudi Arabia. We retrospectively collected data from 182 RRMS patients between 2016 and 2021. A total of 219 relapses were documented in 106 patients (58.2 %). The relapse per patient ratio showed a sinusoidal pattern, peaking in January at a rate of 0.49 and troughed in July at a rate of 0.18. There was no difference in relapse rates between men and women (p =0.280). There was a significant negative correlation between vitamin D levels and relapse rate (r= -0.312, p =0.024). Therefore, the relapse rate was higher during the winter and was correlated with low vitamin D levels. However, relapses are likely multifactorial, and more population-based studies are needed to understand the role of environmental variables in MS exacerbation. A better understanding of this relationship will allow for improved treatment and possibly better prevention of relapse.